Air – water flow through a single serpentine mini channel – flow distribution and pressure drop. (November 2017) - Malhotra, Sneha; Deshpande, Aniruddha; Ghosh, Sumana
Abstract: In the present paper, flow patterns and pressure drop characteristics during air-water flow through a single serpentine mini channel have been studied. Ring flow and slug flow have been observed to be the dominant flow patterns. The flow patterns are majorly surface dominated however, effect of gravity is present at low phase velocities. The pressure drop in vertical orientation is found to be higher than horizontal. Horizontal orientation is more prone to non- uniform distribution of flow regimes.